2012
DOI: 10.1038/ajg.2011.397
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Control of Effector T Cells by Regulatory T Cells: A Clue to Loss of Oral Tolerance and Autoimmunity in Celiac Disease?

Abstract: Our results indicate that effector T lymphocytes from active CD become resistant to suppression by Tregs. This resistance might cause loss of tolerance to gluten, but also to self-antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 35 publications
2
71
1
2
Order By: Relevance
“…In this study we report a higher expression of the alternatively spliced isoform FOXP3 D2 in the intestine of CDA patients compared to non-coeliac controls, while no differences were seen in the expression of FOXP3 FL. Conversely to what was previously reported in the literature [33], our data on CDGF showed a higher expression of both FOXP3 isoforms in this group of patients. Interestingly, however, we found that in CDA patients the relative amount of FOXP3 D2 in the gut mucosa was higher than the FL, while HC subjects and CDGF patients presented a similar expression of both isoforms.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In this study we report a higher expression of the alternatively spliced isoform FOXP3 D2 in the intestine of CDA patients compared to non-coeliac controls, while no differences were seen in the expression of FOXP3 FL. Conversely to what was previously reported in the literature [33], our data on CDGF showed a higher expression of both FOXP3 isoforms in this group of patients. Interestingly, however, we found that in CDA patients the relative amount of FOXP3 D2 in the gut mucosa was higher than the FL, while HC subjects and CDGF patients presented a similar expression of both isoforms.…”
Section: Discussioncontrasting
confidence: 56%
“…While deficiencies in the population of T reg cells have been associated with other autoimmune diseases such as systemic lupus erythematosus (SLE) [28], CD is characterized by an increased number of FoxP3 1 cells in the lamina propria of the small intestine [29,30]. Several groups have shown that their suppressive function is impaired significantly [31][32][33], but the exact mechanisms behind these deficiencies are not understood fully. In the present study, we show that in CD patients the D2 isoform is overexpressed compared to FL in FoxP3-positive cells homing in the gut mucosa and that the intestinal microenvironment, characterized by high production of proinflammatory cytokines and specific microbial-derived metabolites, may contribute to this disequilibrium.…”
Section: Regulatory T Cells (T Reg ) Represent a Subset Of Cd4mentioning
confidence: 99%
“…A human study reported that there were HLA-DQ2.5-restricted, gluten-reactive T R1 cells present in gut biopsies of CD patients, but not control subjects (12). Other human studies reported that LPLs expressing Foxp3, CD25, and CD4 were present at higher frequencies in UCD patients than in control subjects (13,14), and that CD may evolve because of T lymphocytic resistance to suppressive T REG (14). Ag specificity of the presumed T REG was not ascertained in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, such cells were not observed in healthy subjects. Further, it has been demonstrated that there is increased expression of Foxp3 and increased numbers of CD4 + T REG (CD25 + Foxp3 + ) in the smallbowel biopsy specimens of CD patients compared with control subjects (13,14).…”
mentioning
confidence: 99%
“…In CD and CD-related autoimmune diseases a resistance of effector T lymphocytes to suppression by adaptive T reg cells has been demonstrated and has been proposed to explain the loss of immune homeostasis and development of autoimmune responses. Although percentages of CD4+ CD25+ FoxP3 + intraepithelial and lamina propria lymphocytes were significantly higher in patients with active CD compared to healthy controls, proliferation and IFN-γ production of intestinal T lymphocytes were significantly less inhibited by autologous or heterologous T reg cells in CD patients than in controls [70]. Several T reg cells have been found to be important for oral food tolerance: T H 3 cells, a population of CD4+ cells that produce transforming growth factorbeta (TGF-β); T regulatory type 1 (Tr1) cells, which secrete IL-10; CD4+ CD25+ regulatory T-cells, which express the transcription factor forkhead/winged-helix transcription factor box protein 3 (FoxP3); CD8+ suppressor T-cells; and gammadelta T-cells.…”
Section: Non-celiac Gluten Sensitivitymentioning
confidence: 92%